2018
DOI: 10.1186/s12896-018-0433-2
|View full text |Cite
|
Sign up to set email alerts
|

Oil body bound oleosin-rhFGF9 fusion protein expressed in safflower (Carthamus tinctorius L.) stimulates hair growth and wound healing in mice

Abstract: BackgroundFibroblast growth factor 9 (FGF9) is a heparin-binding growth factor, secreted by both mesothelial and epithelial cells, which participates in hair follicle regeneration, wound healing, and bone development. A suitable source of recombinant human FGF9 (rhFGF9) is needed for research into potential clinical applications. We present that expression of oleosin-rhFGF9 fusion protein in safflower (Carthamus tinctorius L.) seeds stimulates hair growth and wound healing.ResultsThe oleosin-rhFGF9 expressed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…Moreover, a natural skin toning cream has been developed from safflower oil [55]. The oil body bound oleosin-rhFGF9 expressed in safflower seed stimulates hair growth and wound healing in mice [56]. Dakhil et al [57] have reported that safflower oil characteristics can make it a main ingredient in the preparation of topical agents for the treatment of various skin problems.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a natural skin toning cream has been developed from safflower oil [55]. The oil body bound oleosin-rhFGF9 expressed in safflower seed stimulates hair growth and wound healing in mice [56]. Dakhil et al [57] have reported that safflower oil characteristics can make it a main ingredient in the preparation of topical agents for the treatment of various skin problems.…”
Section: Discussionmentioning
confidence: 99%
“…The idea of using fusion protein as a delivery vehicle to effectively control the release of growth factors have been reported but mainly on the skin defects repairing [44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The lipophilic nature of oil bodies makes them easy to separate from the aqueous extraction medium by floating centrifugation, which simplifies downstream processing [ 95 ]. This technology has enabled the accumulation of proteins such as β-glucuronidase (the first to be reported), xylanase and hirudin in Brassica napus seeds [ 95 , 96 , 97 ], insulin, human fibroblast growth factor 9 (hFGF-9) and hEGF in Arabidopsis thaliana seeds [ 98 , 99 , 100 ], and hFGF-9, hEGF and antimicrobial peptides in safflower seeds [ 66 , 67 , 101 , 102 ]. All of these proteins remained functional in vitro.…”
Section: Plant-derived Microparticles: Storage Organelles For Bioencapsulationmentioning
confidence: 99%
“…All of these proteins remained functional in vitro. The emulsifying properties of oil bodies in safflower seeds were shown to promote absorption when topically applied to the skin of wounded rodents [ 66 ]. The transdermal drug delivery of oil body-linked hEGF significantly accelerated wound healing and tissue regeneration, and the mechanism may be similar to that seen with drugs delivered via liposomes [ 66 ].…”
Section: Plant-derived Microparticles: Storage Organelles For Bioencapsulationmentioning
confidence: 99%
See 1 more Smart Citation